Is response time predictive of choice? An experimental study of threshold strategies - Andrew Schotter; Isabel Trevino (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
This paper investigates the usefulness of non-choice data, namely response times, as a predictor of threshold behavior in a simple global game experiment. Our results indicate that the signal associated to the highest or second highest response time at the beginning of the experiment are both unbiased estimates of the threshold employed by subjects at the end of the experiment. This predictive ability is lost when we move to the third or higher response times. Moreover, the response time predictions are better predictors of observed behavior than the equilibrium predictions of the game. They are also robust, in the sense that they characterize behavior in an out-of-treatment exercise where we use the strategy method to elicit thresholds. This paper is the first to point out the predictive power of response times in a strategic situation.
Keywords: C71; C9; D03; D89; 330; response time; threshold strategies; global games